2003
DOI: 10.3122/jabfm.16.4.278
|View full text |Cite
|
Sign up to set email alerts
|

The Content of a Low-income, Uninsured Primary Care Population: Including the Patient Agenda

Abstract: Background: Poor and uninsured people have increased risk of medical and psychiatric illness, but they might be more reluctant to seek care than those with higher incomes. Little information exists about the biopsychosocial problems and concerns of this population in primary care.Methods: We surveyed 500 consecutive patients (aged 18 to 64 years) in a primary care clinic serving only uninsured, low-income patients. We used self-report questions about why patients were coming to the clinic, a chronic illness qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 75 publications
0
15
0
Order By: Relevance
“…21,24 Friedman et al 13 found that as many as 42% of patients with LBP in the ER of 1 hospital were unemployed, many of whom were likely uninsured. This same study found that insurance status was associated with decisions to order advanced imaging and that uninsured patients in particular were less likely to undergo such studies.…”
Section: Discussionmentioning
confidence: 99%
“…21,24 Friedman et al 13 found that as many as 42% of patients with LBP in the ER of 1 hospital were unemployed, many of whom were likely uninsured. This same study found that insurance status was associated with decisions to order advanced imaging and that uninsured patients in particular were less likely to undergo such studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although associations between mental illness and chronic diseases are well recognized, 17 the possible synergistic infl uence of multimorbidity and poverty on psychological distress is less well documented. 18,19 Almost one-third (30%) of patients in the most deprived areas wanted to discuss psychosocial problems, and almost two-thirds (65%) of these patients expected to discuss more than 1 problem. Interventions aimed at increasing the number of problems voiced by patients 20 need to take account of the substantial increases in physician time that would be likely be required to meet such demands in the most deprived areas.…”
Section: Mean Stressmentioning
confidence: 99%
“…25 Indigent persons tend to have more medical and mental health problems and decreased psychological, social, and physical functioning. 26 For example, headache, chronic back pain, and arthritis were the most frequent complaints among poor and uninsured patients; and depression and anxiety were associated with a higher prevalence of pain. Pain complaints were inversely related to income; low income also negatively influenced access to care for chronic pain.…”
Section: Pain and Low Incomementioning
confidence: 99%
“…Pain complaints were inversely related to income; low income also negatively influenced access to care for chronic pain. 25,26 Emotional and behavioral responses to chronic pain were determined in part by the patient's appraisal of and strategies for coping with pain problems. 27 Racial and ethnic disparities are often considered with income and influence the pain experience.…”
Section: Pain and Low Incomementioning
confidence: 99%